Foliar application of nitrogen and molybdenum in sugarcane - Altarugio, Lucas Miguel (2023)
Nitrogen (N) management directly impacts the carbon balance in the production of bioenergy from sugarcane. To increase the efficiency of nitrogen fertilization, foliar fertilization with N has been adopted, together with molybdenum (Mo), which can favor N assimilation by participating in nitrate reductase. The hypothesis of this research is that foliar fertilization with N, associated with Mo, increases N use efficiency (EUN) and sugarcane yield. Two experiments were carried out in nutrient solution and also experiments in the field. The first experiment in nutrient solution evaluated foliar application of N-urea in plants with different N supplies (0.75; 1.5; 3.0; 7.5 and 15.0 mM of N). The foliar fertilization with N increased the dry mass of the leaves and the total N content by 128% only in the plants supplied with 3.0 mM of N and that presented greater development at the time of application. The second experiment in nutrient solution evaluated the recovery of 15N foliar applied in plants with or without N deficiencies. The foliar application of N increased the dry biomass by 5.1%, but no interaction with Mo was observed. The recovery of 15N foliar applied application was 29.5 and 36%, respectively, for deficient plants and those with an adequate supply of N. Finally, five field experiments were installed, evaluated by two agricultural seasons, totaling 10 harvests, evaluating rates of N and Mo applied via foliar application at the maximum development stage (December-January). In the crop subject to water deficit, foliar fertilization with N and Mo had little influence on sugarcane yield. Under adequate water conditions, in the average of five locations, the application of 5 kg ha-1 N increased sugarcane productivity by 6 Mg ha-1 . The rates of 10 and 20 kg ha-1 did not promote an increase in sugarcane yield. Mo contributed little to the increase in yield, although it increased the sugar content of the plant in the dry year. Foliar fertilization with N has the potential to increase sugarcane productivity under field conditions, although the association of Mo with N-urea was not very effective in improving N-urea recovery and sugarcane yield.